2020
DOI: 10.1002/dmrr.3301
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glycaemic variability and cardiovascular autonomic dysfunction in patients with type 1 diabetes: A systematic review

Abstract: Rigorous glycaemic control -reflected by low HbA1c goals -is of utmost importance in the prevention and management of complications in patients with type 1 diabetes mellitus (T1DM). However, previous studies suggested that short-term glycaemic variability (GV) is important to consider as well, as excessive glucose fluctuations may have an additional impact on the development of diabetic complications. The potential relationship between GV and the risk for cardiovascular autonomic neuropathy (CAN), a clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…Another phenomenon that could hypothetically alter the relationship between GV and mood is impaired cardiovascular autonomic modulation, 39,40 as is the case in cardiovascular autonomic neuropathy, one of the complications of diabetes. 41 Understanding interindividual differences in emotional reactivity to GV could help predict which persons with diabetes could profit most from more stable blood glucose levels in terms of their emotional health.…”
Section: Discussionmentioning
confidence: 99%
“…Another phenomenon that could hypothetically alter the relationship between GV and mood is impaired cardiovascular autonomic modulation, 39,40 as is the case in cardiovascular autonomic neuropathy, one of the complications of diabetes. 41 Understanding interindividual differences in emotional reactivity to GV could help predict which persons with diabetes could profit most from more stable blood glucose levels in terms of their emotional health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical exercise has been proved to improve HRV in patients with diabetes [21]. Although HRV is not an obligatory measurement in the management of diabetes, it has a predictive and prognostic value owing to its association with diabetic complications and mortality [22]. Inappropriate management of diabetes results both in increased HbA1c levels and hypoglycemic attacks, which is linked to reduced HRV levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been recognized that an essential parameter to consider when evaluating GV, which would facilitate safe and effective therapeutic decision making, is also the time spent in the various glycemic ranges (i.e., time per day within target glucose range (TIR), time below target glucose range (TBR), and time above target glucose range (TAR) [23]. Since each index has its limitations, to better compare data across different studies, the clinical community should design standardized guidelines to precisely measure GV [24]. Achieving this goal will be a key point to identify the biological mechanisms underlying GV.…”
Section: Glycemic Variability and Clinical Implicationsmentioning
confidence: 99%
“…The association between GV and increased risk of cardiovascular complications, such as cardiovascular autonomic neuropathy (CAN) in T1DM, was exanimated in a recently published systematic review [24]. This review showed high heterogeneity in the methodological approaches of different studies, and thus, it is difficult to compare them and come to an unambiguous conclusion regarding GV implication.…”
Section: Glycemic Variability In Patients With Type 1 Diabetes (T1dm) and Cardiovascular Complicationsmentioning
confidence: 99%